452 Supplementation of Saccharomyces cerevisiae boulardii and an antibiotic growth promoter affects bacterial composition of the gastrointestinal tract of calves during the pre- and post-weaning periods. (7th December 2018) - Fomenky, B; Do, D; Talbot, G; Bissonnette, N; Lessard, M; Chouinard, Y; Ibeagha-Awemu, E
Abstract: The gastrointestinal tract (GIT) microbiota has attracted much attention due to its impact on animal health and productivity. This study characterized the GIT bacterial communities of calves (8/treatment) supplemented with Saccharomyces cerevisiae boulardii CNCM1-1079 (SCB) (7.5x108CFU/L milk replacer + 3x109CFU/kg feed) or an antibiotic (ATB) (chlortetracycline (528mg/L)/neomycin (357mg/L) pre-weaning and chlortetracyclin (55mg/kg) post-weaning) or not supplemented (CTL). Twelve calves (4/treatment) were euthanized on day33 (pre-weaning) and another 12 (4/treatment) on day96 (post-weaning) for collection of digesta from rumen (RuD), ileum (IlD) and colon (CoD), and mucosa from ileum (IlM) and colon (CoM). Extracted DNA was subjected to amplicon sequencing of the V3–V4 region of the 16S rRNA gene (Illumina MiSeq) followed by bioinformatics with QIIME pipeline. Abundance at genus level was compared between treatments using DESeq2. Functional analyses of inferred genes were performed using PICRUSt software. Pre-weaning, SCB and ATB significantly reduced(p.FDR≤5.97E-03) Streptococcus abundance in CoM meanwhile SCB reduced Tyzzerella_4 (p.FDR=4.27E-09) in IlM compared to CTL. Post-weaning, SCB increased (p.FDR≤7.01E-04) Fibrobacter and Roseburia while ATB increased (p.FDR≤5.15E-03) Dorea and Anearovibrio compared to CTL. SCB treatment significantly (p<0.05) influenced six pathways in IlM and five pathways in RuD during pre-weaning. ATB treatment significantly changed the abundance of thyroid hormone signaling and lipid metabolism pathways in IlD, cAMP signaling in CoM and RIG-I-like receptor signaling, D-arginine/D-ornithine metabolism and butanoate metabolism pathways in IlM. ATB and SCB affected the bacterial communities of IlM, IlD, CoM, and RuD. In addition, SCB and ATB treatment shared common mechanisms like bile secretion in IlM, steroid biosynthesis, and cAMP signaling in RuD. However, SCB affected more GIT sites and pathways compared to ATB. This study indicates that SCB and ATB mostly influenced different bacterial communities in different GIT sites during the pre- or post-weaning periods. Thus, SCB deserves attention as a probable alternative to antibiotics growth promoter.